Health Worker mHealth Utilization: A Systematic Review. Issue 5 (May 2016) - White, Alice; Thomas, Deborah S.K.; Ezeanochie, Nnamdi; Bull, Sheana
Abstract : This systematic review describes mHealth interventions directed at healthcare workers in low-resource settings from the PubMed database from March 2009 to May 2015. Thirty-one articles were selected for final review. Four categories emerged from the reviewed articles: data collection during patient visits, communication between health workers and patients, communication between health workers, and public health surveillance. Most studies used a combination of quantitative and qualitative methods to assess acceptability of use, barriers to use, changes in healthcare delivery, and improved health outcomes. Few papers included theory explicitly to guide development and evaluation of their mHealth programs. Overall, evidence indicated that mobile technology tools, such as smartphones and tablets, substantially benefit healthcare workers, their patients, and healthcare delivery. Limitations to mHealth tools included insufficient program use and sustainability, unreliable Internet and electricity, and security issues. Despite these limitations, this systematic review demonstrates the utility of using mHealth in low-resource settings and the potential for widespread health system improvements using technology.